1992
DOI: 10.1111/j.1365-294x.1992.tb00155.x
|View full text |Cite
|
Sign up to set email alerts
|

Applications of random amplified polymorphic DNA (RAPD) in molecular ecology

Abstract: Molecular genetic markers have been developed into powerful tools to analyse genetic relationships and genetic diversity. As an extension to the variety of existing techniques using polymorphic DNA markers, the Random Amplified Polymorphic DNA (RAPD) technique may be used in molecular ecology to determine taxonomic identity, assess kinship relationships, analyse mixed genome samples, and create specific probes. Main advantages of the RAPD technology include (i) suitability for work on anonymous genomes, (ii) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
440
1
22

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 840 publications
(479 citation statements)
references
References 33 publications
9
440
1
22
Order By: Relevance
“…because the genotype is not influenced by environmental factors, evolution of closely related taxa can be investigated from an objective point of view with molecular techniques (Hillis, 1987). In addition, some molecular marker assays, e.g., the use of random amplified polymorphic DNA (RAPD), allow the detection of DNA polymorphisms by randomly amplifying multiple regions of the genome by polymerase chain reaction (PCR) using single arbitrary primers designed independently of target DNA sequence (Welsh & McClelland, 1990;Hadry et al, 1992;Williams et al, 1993;Karp et al, 1996). Therefore, it has been extensively used as a genetic marker for estimating genetic, taxonomic, and phylogenetic relationships of plants and animals (Williams et al, 1990;Wachira et al, 1995;Kapteyn & Simon, 2002;belaj et al, 2003;Deshwall et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…because the genotype is not influenced by environmental factors, evolution of closely related taxa can be investigated from an objective point of view with molecular techniques (Hillis, 1987). In addition, some molecular marker assays, e.g., the use of random amplified polymorphic DNA (RAPD), allow the detection of DNA polymorphisms by randomly amplifying multiple regions of the genome by polymerase chain reaction (PCR) using single arbitrary primers designed independently of target DNA sequence (Welsh & McClelland, 1990;Hadry et al, 1992;Williams et al, 1993;Karp et al, 1996). Therefore, it has been extensively used as a genetic marker for estimating genetic, taxonomic, and phylogenetic relationships of plants and animals (Williams et al, 1990;Wachira et al, 1995;Kapteyn & Simon, 2002;belaj et al, 2003;Deshwall et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Distance methods are most commonly used, although principal coordinate analysis (a multivariate analysis of overall similarity) is also common. The nature of the data set seems suitable for parsimony (Hadrys et a!., 1992), but this is not often used. Stiles et al (1993) found different distance measures gave a similar result, consistent with tradi-…”
Section: Discussionmentioning
confidence: 99%
“…Molecular identification based on DNA cloning and sequencing has been considered to be a more efficient, faster way compared to the conventional identification methods, such as SSR (simple sequence repeat: Zietkiewicz et al, 1994) method for mono-locus analysis of microsatellites, RAPD (random amplified polymorphic DNA: Hadrys et al, 1992), ISSR (inter simple sequence repeat: Nagaoka et al, 1997) and AFLP (amplified fragment length polymorphism: Vekemans et al, 2002), through which larger portion of the genome can be studied. Among various molecular identification means, the sequence analysis of internal transcribed spacer (ITS: Sang et al, 1995), a region of ribosomal RNA is considered to be an effective method.…”
Section: Introductionmentioning
confidence: 99%